Validation of electromagnetic and hadronic physical processes in the interaction of a proton beam with matter: A Solar Particle Events case study with an Al slab. Issue 1 (1st January 2017) - Loffredo, Filomena; Vardaci, Emanuele; Quarto, Maria; Roca, Vincenzo; Pugliese, Mariagabriella
Abstract: In the study of the effectiveness of shielding materials against radiations, one of the main steps concerns with the validation of models describing the interaction processes of the radiation of interest with the material chosen for the shielding. This paper shows the results of the validation of electromagnetic and hadronic processes with the aim to contribute to the study of protection for astronauts against the radiations due to the Solar Particle Events, in particular to the selection of the optimal material for radiation shielding. The physics case deals with the interaction of a proton beam with an aluminum slab about 20 g/cm 2 thick. Two specific applications, STP and DOSE, were developed by using Geant4 package. STP computes the radiations produced in the interaction and their stopping power; DOSE computes the absorbed dose from the stopping power calculated by STP. The validation process was performed in two steps. In the first one, the output of the STP code is compared to data available on NIST database; in the second one, the absorbed dose computed with DOSE is compared to the dose gathered during an experiment performed at the NASA Space Radiation Laboratory involving the bombardment of an aluminum slab with a 1 GeV proton beam. The computing model has allowed us to correlate the size of the impinging beam profile to the dose measured before and after an Al slab. The sharp increase of the dose in the position right after the slab might be due to the stochastic nature of the trajectories of charged ions in matter which makes the radiation to emerge with non-zero transverse linear momentum. From the case examined here, we conclude that aluminum is not an efficient material for Solar Particle Event shielding.